PENGARUH DIVERSITAS DEWAN KOMISARIS DAN DIREKSI PADA TAX AVOIDANCE - Dewi, Gede Krisna (E-Jurnal Akuntansi, 2017)
This research aims to examine the effect of board diversity to tax avoidance. This research took finance companies which is listed in Indonesian Stock Exchange period 2010-2014 as a research sample. The result obtained by purposive sampling is 30 companies which are fit with the sample criteria. The hypothesis tested by using multiple regression analysis. The result of hypothesis testing shows that presence of native on the board (nationality diversity) and proportion of outside director influence tax avoidance. Firm size as a control variable is also has no effect to tax avoidance.
Keywords: board diversity, tax avoidance, corporate governance